Ready or not, here i come: a scoping review of methods used to assess player readiness via indicators of neuromuscular function in football code athletes - Guthrie, B.; Jagim, A. R.; Jones, M. T. (Strength and Conditioning Journal, 2023)
A scoping review methodology was used to assess player readiness via indicators of neuromuscular function in response to training load. Literature search included PubMed, Web of Science, SportDiscus, and CINAHL. Search strategy was based on Population-Concept-Context framework evaluating football code athletes with the focus on player readiness in the context of longitudinal monitoring across quantified training loads with an emphasis on neuromuscular function. Demographics, frequency of data collection, methods of monitoring readiness, neuromuscular function, duration of monitoring period, and quantification of training loads were reported. Authors independently reviewed articles and, in the case of disagreement, a vote determined inclusion. The sports of rugby (n = 13) and soccer (n = 11) were most frequently examined, followed by Australian Rules Football (n = 6) and American Football (n = 1). The most common methods assessed systemic readiness with the primary focus on jump and sprint testing. Findings identified limited evidence supporting structural and tissue-specific monitoring tools. Player readiness assessment strategies have evolved with advances in technology and analytics. It is recommended that future research focus on a variety of populations, including youth and women athletes. This review is the first to summarize methods of assessing player readiness using indicators of neuromuscular function in football code athletes.